Liberating the people from their “loathsome practices:” public health and “silent racism” in post-revolutionary Bolivia - Nicole L. Pacino (História, Ciências, Saúde: Manguinhos)
Abstract: After the Movimiento Nacionalista Revolucionario (MNR) took power in the 1952 National Revolution, the party expanded rural public health programs to address what early twentieth-century elites called the “Indian problem:” the idea that indigenous culture was an impediment to Bolivia’s modernization. After 1952, the MNR used public health as a project of cultural assimilation, and state-sponsored health programs sought to culturally whiten the population by transforming personal habits. This essay analyzes the language with which health workers discussed the indigenous population to show that despite the regime’s intention to move away from defining the rural population on racial terms, medical and political elites continued to define indigenous customs as an obstacle to progress and a remnant of an antiquated past.